Anesthetic and Hemodynamic Effects of Continuous Spinal and Epidural Anesthesia - Erbüyün, Koray; Ok, Gülay; Tekin, İdil (Fırat University, 2007)
Objectives: It was aimed to compare the effects of epidural and continuous spinal anesthesia. Material and Methods: In 35 patients who were to be operated from lower extremities, epidural anesthesia was performed in groupI (n=18) and continuous spinal anesthesia in groupII (n=17). 15 mL(300 mg) of 2%prilocaine as initial dose and 5 mL (100 mg) as additional dose was administered in the group I; in the group II the initial dose was 2.5 mL(50 mg), and additional dose 1mL (20 mg). Hemodynamic parameters, sensorial and motor block levels were recorded every 5 minutes. Intraoperative complications were watched for. Results: Heart rate(HR) and blood pressure(BP) was found to be lower than basal values after the 10.min in group I., HR and BP after 45.min in the group II. Time for sensorial blockade commencement was found to be longer in group I compared to group II.. Duration of sensorial blockade was not found to be different between groups. Motor blockade did not happen in the group I; motor blockade occured in all cases of group II. Conclusion: It is concluded that continuous spinal compared to epidural anesthesia, improved patient comfort by providing better hemodynamic stability and motor blockade with less local anesthetic dose, by affecting faster and causing fewer intraoperative complications, but more technical problems might be encountered. ©2007, Firat University, Medical Faculty

Giriş: Epidural ve sürekli spinal anestezi uygulamasının etkilerinin karşılaştırılması amaçlandı. Gereç ve Yöntem: Alt ekstremite operasyonu yapılacak 35 olguda, I. gruba (n=18) epidural, II. gruba (n=17) sürekli spinal anestezi uygulandı. % 2'lik prilokainden; I. gruba, başlangıç dozu 15 mL (300 mg), ek doz 5 mL (100 mg); II. gruba, başlangıç dozu 2.5 mL (50 mg), ek doz 1mL (20 mg) verildi. Hemodinamik parametreler, duyusal ve motor blok seviyeleri beş dakikada bir kaydedildi. Peroperatif komplikasyonlar izlendi. Bulgular: Kalp atım hızı ve kan basıncı, I. grupta 10., II. grupta 45. dakikadan sonra bazal değere göre düşük bulundu. Duyusal blok başlangıç süresi, I. grupta, II. gruba göre uzun bulundu. Duyusal blok etki süresi gruplar arasında farklı bulunmadı. I. grupta motor blok oluşmadı, II. gruptaki olguların tamamında motor blok gerçekleşti. Sonuç: Epidural anesteziye göre sürekli spinal anestezinin, düşük lokal anestezik dozuyla daha iyi hemodinamik stabilite ve motor blok sağlayarak, daha hızlı etkileyerek ve daha az peroperatif komplikasyona neden olarak hasta konforunu artırdığı ancak daha fazla teknik sorunla karşılaşılabileceği sonucuna varıldı. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Sürekli Spinal ve Epidural Anestezi Yöntemlerinin Anestezik ve Hemodinamik Etkilerinin Karşılaştırılması